2018
DOI: 10.1016/j.electacta.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of drug loading capacity and release characteristics of PEDOT/naproxen system: Effect of doping ions

Abstract: Conducting polymers are versatile and robust materials that have recently become attractive as controlled drug delivery systems. Possessing ion exchangeable properties, they can serve as carriers for numerous biologically active species, showing particular applicability in neural tissue engineering and regional chemotherapy. In the pursuit of the design of the most effective controlled drug delivery system, we aimed to compare the performance of the conducting polymer-based matrix as a function of doping anion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 69 publications
2
11
0
Order By: Relevance
“…SEM imaging (Figure 3A) revealed that PEDOT derived coatings possessed a porous and rough surface structure as previously reported [34]. Conducting electropolymerization in the presence of Dex induced a modest change in morphology and the formation of larger grains were observed [35,36].…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…SEM imaging (Figure 3A) revealed that PEDOT derived coatings possessed a porous and rough surface structure as previously reported [34]. Conducting electropolymerization in the presence of Dex induced a modest change in morphology and the formation of larger grains were observed [35,36].…”
Section: Resultssupporting
confidence: 74%
“…Negatively charged drugs, such as Dex, are typically immobilized during oxidative polymerization of EDOT, and consecutively released during the spontaneous dedoping of the polymer [6]. The kinetics of the release is the function of the physicochemical parameters of the polymer coating, such as its porosity, morphology and ion exchange capacity, as well as the properties of the drug itself, including ion size and mobility, and can be facilitated by an external stimuli, e.g., an electrical potential [34].…”
Section: Resultsmentioning
confidence: 99%
“…The result is a highly controlled release mechanism, which is entirely localized only to the site of implantation. Researchers use conducting polymer‐based drug delivery to release therapeutics, dyes, and neurotransmitters and neuromodulators …”
Section: Introductionmentioning
confidence: 99%
“…It can also be inferred that positively charged PEDOP oligomers are attracted by the negatively charged structural units of PSS, resulting in the stacked arrangement of pyrrole rings, as in a case of PEDOT/PSS[45,46]. Conversely, the surface of PEDOP films doped with smaller ions (chlorides/phosphates and PTS), was composed of polymer grains regularly dispersed over the Pt surface, in a similar way as observed for PEDOT[7,24]. These matrices exhibited also high values of roughness (R a of 96.5 nm and 215 nm for PEDOP/PBS and PEDOP/PTS, respectively), which had the effect on the wettability of the surfaces.…”
mentioning
confidence: 70%
“…The doping ion is used to maintain the electroneutrality of the polymer, since the process of polymerization involves the formation of radical cations [23]. Through the choice of dopant, it is possible to tailor such properties as electrical conductivity [24], surface morphology [25] and polymer elasticity [26], considerations for the design of a neural interface technologies. The most well studied dopants for oxidative polymerization include buffer salts and perchlorates, and more recently, aromatic sulfonate compounds, such as p-toluenesulfonate (PTS) and polystyrene sulfonate (PSS) [5].…”
Section: Introductionmentioning
confidence: 99%